HEART RATE VARIABILITY AS A NON-INVASIVE CARDIO-AUTONOMIC BIOMARKER FOR SLEEP DISORDER AND COGNITIVE DECLINE IN EPILEPSY: A LITERATURE REVIEW - Pikatan, Orlando; Indrasari Utami, Desak Ketut; Ayu Putri Laksmidewi, Anak Agung; Meidiary, Anak Agung Ayu; Arimbawa, I Komang; Widyantara, I Wayan (MNJ (Malang Neurology Journal), 2026)
Background: Epilepsy is a chronic neurological disorder affecting over 50 million people worldwide, often compounded by significant but undertreated comorbidities such as sleep disturbances and cognitive impairment. Heart Rate Variability (HRV), a non-invasive biomarker for the dynamic balance of the autonomic nervous system, has emerged as a potential physiological link connecting these seemingly disparate symptoms. Methods: This literature review systematically synthesized recent evidence from peer-reviewed publications, with a primary focus on research published after 2020, to investigate the intricate, bidirectional relationship between HRV, sleep, and cognition in the context of epilepsy. Results: The findings consistently demonstrate that patients with epilepsy exhibit significantly lower HRV compared to healthy controls, reflecting a persistent state of sympathetic dominance. This underlying autonomic imbalance is identified as a central pathophysiological mechanism that not only contributes to poor sleep quality and cognitive deficits but also increases the risk of Sudden Unexpected Death in Epilepsy (SUDEP). This review posits. HRV as a crucial, non-invasive biomarker for comprehensive risk stratification, suggesting that targeted interventions aimed at restoring autonomic balance, such as cognitive behavioral therapy for insomnia (CBT-I) and vagus nerve stimulation (VNS), hold significant promise for improving overall patient quality of life. Conclusion: this review establishes low HRV as a key marker of a shared pathological mechanism in epilepsy, linking seizure activity with critical sleep and cognitive comorbidities. The potential of HRV as a non-invasive, scalable biomarker for multifaceted risk assessment is substantial. Future research should prioritize large-scale longitudinal studies and controlled trials to standardize HRV measurement and validate targeted interventions that restore autonomic balance, ultimately moving towards a more holistic patient management paradigm.